A Composite Measure of Caregiver Burden in Dementia: The Dementia Burden Scale—Caregiver. Issue 9 (10th August 2018) - Peipert, John D.; Jennings, Lee A.; Hays, Ron D.; Wenger, Neil S.; Keeler, Emmett; Reuben, David B.
Abstract : Objectives: To better capture the scope of caregiver burden by creating a composite of 3 existing measures that assess different health domains. Design: Prospective follow‐up study. Setting: University‐based dementia care management program. Participants: Caregivers of persons with dementia (PWD) (N=1, 091). Measurements: The composite measure (the Dementia Burden Scale—Caregiver (DBS‐CG)) was based on the Modified Caregiver Strain Index, Neuropsychiatric Inventory Questionnaire Distress Scale, and Patient Health Questionnaire (PHQ‐9). Alternative factor structures were evaluated using 2 confirmatory factor analysis (CFA) models: a bifactor model and a 3 correlated factors model. Good model fit was defined as a root mean square error of approximation (RMSEA) of less than 0.06 and comparative fit index (CFI) value greater than 0.95. Coefficient omega was used to estimate scale reliability. Minimally important differences (MIDs) were estimated by anchoring the magnitude of DBS‐CG change to change in caregiver self‐efficacy and functional ability of PWD. Results: The bifactor CFA model fit best (RMSEA = 0.04, CFI = 0.95). Based on this model, a DBS‐CG scale was created wherein all items were transformed to a possible range of 0 to 100 and then averaged. Higher scores indicate higher burden. Mean DBS‐CG score was 27.3. The reliability was excellent (coefficient omega=0.93). MID estimates ranged from 4 to 5 points (effect sizes: 0.20–0.49). Conclusion: This study provides support for the reliability and validity of the DBS‐CG. It can be used as an outcome measure to assess the effect of interventions to reduce dementia caregiver burden.